Religious Existence in the Socio-cultural Communication Context: A Case Study of Ganjuran Temple, Yogyakarta - Qamariyah, Farihatul (IAIN Surakarta, 2017)
This study attempts to describe the symbolic interpretations of Ganjuran temple, the sacred hearth shrine in the context of religious and social construction, with the case study on Ganjuran Church, a Catholic church, the sacred heart of Jesus, in Sumbermulyo village, Bambanglipuro, Bantul-Yogyakarta. Based on the qualitative, wherein the data collected through an in-depth interview for, utilizing the theory of religious symbol and communication including the sacred space by Livingston in the book of Anatomy of Religion as its analytical framework, the result showed that in the case of Ganjuran temple, the sacred hearth shrine in Catholic is the indication of religious existence in the context of social and cultural communication. The symbols of the temple as the sacred Catholic placed in four classifications among the identity aspect; the intersection of traditional prosperity, the image of cultural heritage, and also the space of pilgrimage are the discussions on how this place can be popular in the context of the public environment. Every kind of the interpretation regarding the symbol has a specific significance in the reality, in which, each of them is the sign of communication that denotes a certain issue based on the religious and social construction.Â Keywords:Religion, Symbol, Sacred placeÂ